A Study into Gay Employment and Workplace Discriminations: Hypothesising a multi-pronged approach by reconsidering of the theories and restructuring equality measures - Zhou, Quan (2013)
The argument and denouncement about homosexuality endure for a long time. The social hostility towards homosexuality is often reflected by the workplace discriminations and the under-presentation of gay men/lesbians in the workforce. Within the context of UK, traditional equality approach is the predominant framework for equality actions and it is well-penetrated among organizations. However, the changes in wider economic and political environment and the shifts have had in major concepts, lead to a creation of business driven diversity approach. By emphasizing the positive organizational benefits that diversity can bring, such approach aims to change the initiatives for equality action and substantially creates an organizational inclusive culture. Throughout analyses on both the strengths and weakness of EO and ‘managing diversity’, I attempt to make a critical revaluation on these two frameworks. Meanwhile, primary researches on wider environment and inner organizational policies, as well as first-hand information got from interviews and questionnaires, I try to make my suggestion on building an approach which can provide sounder theory underpin and is more situational-suited.